(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teaching speaking skills in English as a Foreign Language (EFL) classes is a crucial aspect of language learning. Speaking is an essential skill that allows learners to communicate effectively and confidently in real-life situations. This article explores the various strategies and techniques that can be employed by teachers to enhance speaking proficiency among EFL learners.